2013
DOI: 10.1186/1471-2288-13-111
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of a quality appraisal tool for studies of diagnostic reliability (QAREL)

Abstract: BackgroundThe aim of this project was to investigate the reliability of a new 11-item quality appraisal tool for studies of diagnostic reliability (QAREL). The tool was tested on studies reporting the reliability of any physical examination procedure. The reliability of physical examination is a challenging area to study given the complex testing procedures, the range of tests, and lack of procedural standardisation.MethodsThree reviewers used QAREL to independently rate 29 articles, comprising 30 studies, pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 38 publications
0
54
0
3
Order By: Relevance
“…We assessed study quality using a modified quality appraisal tool for studies of diagnostic reliability (QAREL), a tool that has been developed for the assessment of reproducibility studies (16) and found to be reliable (17). Key components of the quality assessment were blinding, the explanation of missing data, and reporting of erroneous results.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…We assessed study quality using a modified quality appraisal tool for studies of diagnostic reliability (QAREL), a tool that has been developed for the assessment of reproducibility studies (16) and found to be reliable (17). Key components of the quality assessment were blinding, the explanation of missing data, and reporting of erroneous results.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…alanlarda tek bir değerlendirici tarafından alınan ölçüm sonuçlarının uyumu/güvenilirliği ya da birden fazla değerlendirici tarafından alınan ölçüm sonuçlarının uyumu/güvenilirliği araştırılmak istenebilir. Ayrıca, klinisyenler, herhangi bir hastalığın tanısının konulmasında, yaygın olarak kullanılan klasik yönteme göre düşük maliyetli ve tedaviye daha kısa bir sürede cevap veren ya da tanının hızlı ve doğru konulduğu bir yöntem bulduklarında, bu yöntemi referans (eski, klasik) yöntem ile karşılaştırarak yöntemlerden elde edilen sonuçların ne derece uyumlu olduklarını belirlemek isteyebilirler 14,15 .…”
Section: Discussionunclassified
“…The CAT-CSS is a reliable tool for evaluating the quality of cross-sectional study design. Lucas et al, 2013 [26], reported that a developed quality appraisal tool for studies of diagnostic reliability showed moderate to high reliability of its criteria. Moreover, the results of reliability of the AGREE instruments indicated that the it was reliable based on the significant agreement of appraisers who tested the instrument [27].Finally, the current results achieved the recommendation of Sanderson, Tatt, & Higgins, 2007 [28],who stated that the tools for assessing research quality should be rigorously developed, valid, reliable, and easy to use.…”
Section: Discussionmentioning
confidence: 99%